Halal awareness as a moderator between halal certification and consumer intention to buy skincare through e-commerce - Basuki, Yasinta Intan Putri; Sjabadhyni, Bertina (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The global halal industry continues to grow, including in sectors such as cosmetics and skincare. This growth is supported by increasing consumer demand for halal products, particularly in Indonesia, which has one of the largest Muslim populations. Ongoing research seeks to understand the factors that influence the intention to purchase halal products. This study aims to examine the effect of halal certification on the intention to purchase halal skincare products, while also investigating the moderating role of halal awareness. Methods: This experimental study involved 310 Muslim female respondents aged 18-25 years. The participants were randomly assigned to either an experimental group, which received a product catalog with halal certification logos, or a control group, which received a catalog without halal certification logos. Following the manipulation, the respondents' intention to purchase and halal awareness were measured. Findings: The results revealed that the intention to purchase was higher in the experimental group compared to the control group, indicating that halal certification positively affects the intention to purchase. However, halal awareness did not moderate this relationship; instead, it had a direct effect on the intention to purchase halal skincare products. Conclusion: Halal certification significantly influences the intention to purchase halal skincare, while halal awareness directly impacts purchasing intention, but not as a moderator. These findings highlight the importance of halal certification in consumer purchasing behavior. Novelty/Originality of This Study: This study contributes to the literature by demonstrating the direct effect of halal awareness on purchasing intention and by providing empirical evidence on the importance of halal certification in the skincare industry, particularly among young Muslim consumers.